Droplet image analysis with user-friendly freeware CellProfiler. Issue 17 (23rd April 2020) - Bartkova, Simona; Vendelin, Marko; Sanka, Immanuel; Pata, Pille; Scheler, Ott
Abstract : We show how to use free open-source CellProfiler for droplet microfluidic image analysis. Abstract : Droplet microfluidic assays are rapidly gaining popularity because they enable analysis of biochemical reactions, individual cells or small cell populations with high sensitivity, precision and accuracy in a high-throughput manner. Nonetheless, there is a demand for user-friendly and low-cost droplet analysis technology. In this article, we meet this demand by developing two droplet analysis pipelines via free open-source software CellProfiler (CP) and its companion (CellProfiler Analyst, CPA). To illustrate the competence of the pipelines as an independent, and freely accessible droplet analysis tool for any researcher without the need of programming skills, we show (i) droplet digital quantification of viable fluorescent bacteria using single-color images and (ii) analysis of a multi-color fluorescence image with droplets containing different chemical compositions.